Influences on Learning, Motivation and Self-Efficacy in the Study of Students at Santo Antonio Catholic Secondary School - martins, Lufiano Tilman; Guterres, Antonio; Silva, Gilberto Guterres da (International Journal of Social Service and Research, 2025)
The purpose of this study was to identify and analyze the influence of learning style, motivation, and confidence on the academic achievement of students at Santo Antonio Alas Catholic High School. This type of research is quantitative research. The population of this study is 90 students at Santo Antonio Alas Catholic High School. The sample of this study is also 90 people. Data collection techniques include observation, questionnaires, and documentation. The data analysis technique included multiple linear regression assumption tests, namely normality, multicollinearity, and heteroscedasticity. In addition, a final statistical test was carried out, namely a hypothesis test with a t-test and an F test. (0.000) < (0.05) and T value (4.928) > table T value (2.000), showing a significant influence of learning style (X1) on student learning achievement (Y). Learning motivation (X2) with a sig value. (0.528) > (0.05) and Tcount (-0.633) < Ttable (2.000) showed that learning motivation (X2) had no significant influence on student learning achievement (Y). Auto-efficacy (X3) with a sig value. (0.000) < (0.05) and Tcount (4.057) > Ttable (2.000) indicate that auto-efficacy (X3) has a significant influence on student learning achievement (Y). The results of the F test with a sig. (0.000) < (0.05) and Fcount (43.591) > Ftable (2.711), indicating that learning style (X1), motivation (X2), and auto-efficacy (X3) simultaneously have a significant influence on student learning achievement (Y).